"The Effects of Silver Nanoparticle Shape on Protein Adsorption and Neural Stem Cell Viability". Issue 39 (19th October 2022) - Kumarasamy, Murali; Tran, Ngoc; Patarroyo, Javier; Mishra, Sushmita; Monopoli, Marco; Madarasz, Emilia; Puntes, Victor
Abstract: Silver nanoparticles (AgNPs) are important and widely used as antimicrobials and nanodrug carriers. The increased use of AgNPs in consumer products has raised concerns about nanosafety; for instance, AgNPs may be inhaled and translocated to the brain via olfactory neural stem cells/progenitors. While the biological effects of nanoparticle size have been widely investigated, there are little data on the effects of particle shape on cellular phenotype. Therefore, here we investigated the interactions between AgNP spheres, rods, cubes, and triangles and human plasma proteins as well as their effects on the viability of NE‐4C neural stem cells. Nanoparticles were synthesized by wet chemistry methods and characterized by UV‐vis spectroscopy, dynamic light scattering, zeta potential measurement, transmission electron microscopy, nanoparticle tracking analysis, and differential centrifugal sedimentation. NE‐4C cell viability was assessed using the MTT reduction assay, and the cellular uptake of differently shaped nanoparticles was monitored by electron microscopy. All 50 nm (in at least one dimension) AgNPs exerted toxic effects, with rods and cubes displaying greater toxicity than spheres and triangles. These cellular and physicochemical results indicate that edges on the AgNPs increase toxicity, presumably due to enhanced ion dissolution from the edges. Abstract : Since the earliest times, silver has been used in everyday life as well as in biomedicine. Despite of the large body of literature precedents, the nano‐size‐caused effects of silver are far from clear. The role of the shape (spheres, cubes, triangles, and rods) of silver nanoparticles (Ag NPs) in interactions with living material and physiological solutions was investigated. Ag NPs with different geometries were prepared and characterized. The dissolution of Ag ions from NPs was monitored by UV‐Vis analysis and the cellular uptake of NPs was investigated by transmission electron microscopy (TEM). Cell viability and cellular uptake studies demonstrated the shape‐dependent toxic effects on NE‐4C neural stem cells with a toxicity rank of spheres< triangles< cubes <rods.